English: Bahasa Indonesia - Wijaya; Eni Rizki Rahayu; Dewi Atikah; Agus Setiyadi; Fajar Adhie Sulistyo; Sasni Triana Putri; Sariaman Purba; Utami Sulistyaningsih (Journal of Health (JoH), 2023)
Dengue Hemorrhagic Fever is a major global problem because 2.5 to 3 billion people are at risk of developing this disease, Aedes Aegypti is the main epidemic vector, a disease that usually affects urban areas, but has begun to attack rural areas, an estimated 50-100 million cases per year. The only program to control the transmission of dengue virus is to fight mosquitoes as dengue vectors. One of the most popular methods is the use of insecticides. The use of insecticides for a certain period of time will cause vector resistance, so it must be used wisely. This study aims to determine the effect of the use of mosquito killers as an alternative to controlling Aedes Aegypti mosquitoes in the working area of ​​the Sindang Barang Health Center. This type of research is an experimental method with a pretest-posttest design, the treatment given is exposure to a mosquito killer device which is divided into 2 groups with different placement hours. The study was conducted in the Sindang Barang Health Center Work Area in August-September 2022 in an area that has the highest incidence of dengue cases, the mosquito killer is placed in a humid and dark corner of the room. The results of the pretest-posttest data on mosquito density obtained a significance value of 0.053, which means that the use of mosquito killers is not effective for controlling Aedes Aegypti mosquitoes.